Information Asymmetry in Business-to-Business Negotiations: A Game Theoretical Approach to Support Purchasing Decisions with Suppliers - Bodendorf, Frank; Hollweck, Barbara; Franke, Jörg (Group Decision and Negotiation, 2022)
The digital transformation confronts purchasing and supply management (PSM) with numerous new challenges, such as digital procurement objects and the information asymmetry between buyers and suppliers. Existing approaches contributing to PSM research (e. g., the selection of suppliers or the calculation of equilibrium prices) have in common that information regarding suppliers (e. g., production costs) must be well-known. However, this information is rarely accessible to purchasers due to the existing information asymmetry. This problem is addressed by a game-theoretical model based on a Stackelberg game to assist PSM in dealing with the information advantage of software suppliers. The applicability in practice is evaluated by a real-world case study from the automotive industry. The results show that the presented model can support decision-making in purchasing by a qualitative analysis of profit scenarios for different negotiation strategies. The model contributes to dismantling the information asymmetry and provides a basis for determining negotiation prices, also for digital procurement objects. This research motivates both supply and purchase managers to jointly optimize their product costs and thus increase their competitiveness on the market.
CRIS-Team WoS Importer:2022-06-24
Keywords: Game theory; Information asymmetry; Decision support; Negotiation; Supply management; Cost management

Technologieorientierte Softwarebewertung zur Unterstützung von Beschaffungsentscheidungen - Bodendorf, Frank; Hollweck, Barbara; Franke, Jörg (Controlling, 2020)
Die Digitalisierung im Automobilbau steigert die Bedeutung der Softwarebeschaffung. Der Einkauf benötigt dabei geeignete Softwarebewertungsmodelle, um bei den Verhandlungen mit Lieferanten die Preistransparenz zu erhöhen. Es wird ein neues Modell vorgestellt, das traditionelle Kostenanalysemethoden mit einer wertorientierten Betrachtung, insb. der Technologieattraktivität, kombinier
Keywords: Automotive Industry; Cost Analysis; Procurement; Software Evaluation; Technology Evaluation